Exploring the Associations between Perceived Organizational Support and Job Burnout among Chinese Academic Journal Editors: A Moderated Mediation Model - Xiaoyan Yu (MDPI AG, 2021)
Background: Job burnout (JB) has become a prevalent emotional and psychological syndrome across diverse contexts, especially in the face of the COVID-19 pandemic. This study aimed to examine the relationship between perceived organizational support (POS), job satisfaction (JS), self-efficacy (SE), and JB, alongside their mechanism of interplay. Methods: We took 210 Chinese academic journal editors as the research participants and designed a moderated mediation model to examine the posited construct. All the data were gathered online and analyzed with the statistical software SPSS and SmartPLS. Results: The participants comprised 117 women (55.71%) and 93 men (44.29%). There were significant differences among observed variables in age, experience, and title. POS had a significant negative predictive effect on JB (95% CI = −0.43; −0.06). JS mediated the relationship between POS and JB (95% CI = −0.48; −0.11). SE moderated the association between JS and JB (95% CI = 0.04; 0.75) but did not function as a moderator in the relationship between POS and JS (95% CI = −0.01; 0.24). Conclusions: POS, JS, and SE were crucial determinants of JB among Chinese academic journal editors. Targeted interventions should be initiated to diminish editors’ feelings of being unappreciated, inefficient, dissatisfied, and unaccomplished at work.